If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 56 = 10log(x) Multiply glo * x 56 = 10glox Solving 56 = 10glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-10glox' to each side of the equation. 56 + -10glox = 10glox + -10glox Combine like terms: 10glox + -10glox = 0 56 + -10glox = 0 Add '-56' to each side of the equation. 56 + -56 + -10glox = 0 + -56 Combine like terms: 56 + -56 = 0 0 + -10glox = 0 + -56 -10glox = 0 + -56 Combine like terms: 0 + -56 = -56 -10glox = -56 Divide each side by '-10lox'. g = 5.6l-1o-1x-1 Simplifying g = 5.6l-1o-1x-1
| 2m=16-9 | | 3c+6=33 | | 14x-3=9x-15 | | -3+6k=9 | | 62+3y=36 | | 36=2.4/(.12-x) | | 1/6-1/3=2/3 | | -4t-7(2t-5)-11=-12 | | 2x+6y-20=0 | | (2x)(x+10)+110=360 | | 5(2x+3)+-3(2+x)=22 | | 2x^2+2y^2-10x-18y=0 | | 10x+-18x=4x-6 | | N-8-7+13=1+4n | | 10x-18x=4-6 | | 5x+9y-4x-4y= | | 300x^14+260x^12+20=0 | | X^2+29x=-54 | | 5(n+4)+24=-2n-8 | | 12/18=n36 | | 11r-6t=45 | | 3x+4(x+1)=2(x+7) | | 3(3x+4)+2(5x-3)= | | 6+2(z-3)=5z+3 | | 12-3x=x-4(2+2x) | | 9(3x+2)+4(x-4)=33 | | 5c-1=39 | | 4(x-1)-x= | | 4(x-1)+x= | | 5(2n+4)=7(9n+2)+1 | | 8h+4=28 | | 3x+2-5x-7=4x+2 |